Inside Greek U. : fraternities, sororities, and the pursuit of pleasure, power, and prestige - DeSantis, Alan D. (Book collections on Project MUSE., 2007)
Popular culture portrays college Greek organizations as a training ground for malevolent young aristocrats. Films such as Animal House, Revenge of the Nerds, Old School, and Legally Blonde reinforce this stereotype, but they fail to depict the enduring influence of these organizations on their members. Inside Greek U. provides an in-depth investigation of how fraternities and sororities bolster traditional, and potentially damaging, definitions of gender and sexuality. Using evidence gathered in hundreds of focus group sessions and personal interviews, as well as his years of experience as a faculty advisor to Greek organizations, Alan D. DeSantis offers unprecedented access to the world of fraternities and sororities. DeSantis, himself once as member of a fraternity, shows the profoundly limited gender roles available to Greeks: "real men" are taught to be unemotional, sexually promiscuous, and violent; "nice girls," to be nurturing, domestic, and pure. These rigid formulations often lead to destructive attitudes and behaviors, such as eating disorders, date rape, sexual misconduct, and homophobia. Inside Greek U. shows that the Greek experience does not end on graduation day, but that these narrow definitions of gender and sexuality impede students' intellectual and emotional development and limit their range of choices long after graduation. Ten percent of all college students join a Greek organization, and many of the nation's business and political leaders are former members. DeSantis acknowledges that thousands of students join Greek organizations each year in search of meaning, acceptance, friendship, and engagement, and he illuminates the pressures and challenges that contemporary college students face. Inside Greek U. demonstrates how deeply Greek organizations influence their members and suggests how, with reform the worst excesses of the system, fraternities and sororities could serve as a positive influence on individuals and campus life.